Analysing the Impact of MOODLE and its Modules on Students Learning,A Case Study in Mechanical Engineering - Kulkarni, Trishul P.; Toksha, Bhagwan G.; Bhosle, Santosh P.; Deshmukh, Bijlee (Journal of Engineering Education Transformations, 2019)
A systematic study is carried out as a specific case on analyzing the impact of ICT tool particularly MOODLE and its modules on students learning. Course named Manufacturing Processes offered in fourth semester of degree program in Mechanical Engineering is selected. A course offering is made through blended mode consisting conventional face to face learning and online learning through MOODLE and compared with control group. This paper reports the effectiveness of using technology in blended fashion over the conventional face to face learning. Success rate in content based test is found to be 21% more over the control group. Statistical parameters evaluated for content based test are found in favor of strong participation with the tvalue 2.617, the P-Value is 0.013. The result is significant at p < 0.05. A post course survey is employed to analyze the effectiveness and acceptance among participants about various MOODLE modules.